Do tax incentives affect investment quality? - Eichfelder, Sebastian; Jacob, Martin; Schneider, Kerstin (Journal of Corporate Finance, 2023)
This paper examines the effect of tax incentives in the form of bonus depreciation on investment quality. Using the expiration of tax incentives via bonus depreciation in eastern Germany and a representative panel of West German establishments, we show that bonus depreciation significantly lowers investment quality. The average quality of investments, measured by the responsiveness of future revenue and other proxies for cash flow to current investment, reduces by 15.2–23.8% in the short run and 31.8–41.4% in the long run. Our research suggests that this adverse effect of tax subsidies is greater for jurisdictions with higher tax rates, in times of high unemployment, and for large or low-productivity establishments. Overall, while increasing investment quantity, as shown by prior literature, tax incentives such as bonus depreciation substantially reduce the quality of investments.